Pengaruh Pengeluaran Lembaga Non-Profit Rumah Tangga Dan Perubahan Inventori Terhadap Pertumbuhan Ekonomi Provinsi Nusa Tenggara Barat - Bahri Nurjan; Indah Fitriana Sari (CV. Ulil Albab Corp, 2023)
This study aims to determine the effect of spending on household non-profit institutions and inventory changes on economic growth in West Nusa Tenggara Province from 2019 to 2022 using panel data regression with a total of 10 districts/cities in West Nusa Tenggara Province using the eviews 12 program. The data used are secondary data sourced from the official website of the Statistics Indonesia. The estimation used in this study is the Fixed Effect (FEM) model. The results showed that the household non-profit expenditure variable (X1) had a positive but not significant effect on economic growth, while the inventory change variable (X2) had a positive but not significant effect on economic growth. In addition, simultaneously the expenditure variables of household non-profit institutions (X1) and inventory changes (X2) have a significant or jointly significant effect on economic growth (Y) in West Nusa Tenggara Province in 2019-2022.